Clinical Relevance of Age-Related Immune Dysfunction - Castle, Steven C. (Clinical infectious diseases, 2000)
Immunosenescence is the state of dysregulated immune function that contributes to the increased susceptibility to infection of the elderly. Extensive studies of inbred laboratory animals and very healthy elderly humans have identified changes in immunity; these studies have identified limited phenotypic and functional changes in the T cell component of adaptive immunity. However, no compelling scientific evidence has shown that these changes have direct relevance to the common infections seen in the aged population. This perspective will attempt to shed light on this dilemma. First, it will review clinically relevant infections in the elderly, focusing on influenza and influenza virus vaccination and how chronic illness contributes to increased risk and severity of infection and/or failed vaccine response. Second, key changes in immunity will be reviewed, keeping a perspective of the impact of confounding variables in addition to age but focusing on age-related changes in the interaction of the innate and acquired components of immunity. If the goal is to prevent serious infections in the elderly, it appears that the field of geriatric immunology and/or infectious diseases is faced with the tremendous challenge of studying a very diverse population, including mildly immunocompromised/chronically ill individuals and very healthy elderly.